Prevalent genetic alterations in pediatric thyroid carcinoma: Insights from an Argentinean study - Sandra Lorena Colli; Marisa Esther Boycho; Patricia Papendieck; Franco Mauricio Mangone; Ana Chiesa; Mercedes García Lombardi; Martín Medín; Elena Noemí De Matteo; Mario Alejandro Lorenzetti; María Victoria Preciado (PLoS ONE, 2025)
Thyroid cancer is the primary endocrine malignancy, exhibiting distinct genomic drivers. The frequency of genetic alterations varies between adult and pediatric groups and across geographic regions and ethnicities. Molecular markers may serve as prognostic tools and/or specific treatment-selection tools in papillary thyroid carcinoma (PTC) in children. We sought to characterize molecular alterations in pediatric PTC from Argentina and test a future laboratory algorithm for molecular diagnosis and stratification. Immunohistochemistry, fluorescence in situ hybridization, and Sanger sequencing were performed on 57 pediatric PTC samples. This study assesses multiple genetic alterations, including fusions in RET, ALK, MET, BRAF, and NTRK genes, as well as the BRAF V600E single nucleotide variant. Fusions in known oncogenes were observed in 29.8% of cases (6 in RET, 5 in ALK, 4 in NTRK3, 1 in BRAF, and 1 in MET). The BRAF V600E SNV was detected in 12.3% of cases. Larger tumor size and higher initial risk were associated with genetic alterations (P = 0.027 and P = 0. 036, respectively). Designing a laboratory algorithm following an increasing order of complexity provided a reliable molecular testing platform that reduces the requirement for NGS screening. These results also broaden the data on PTC alterations in children from Argentina.